STAGES OF FORMATION AND DEVELOPMENT OF THE NATIONAL CURRENCY OF THE REPUBLIC OF KAZAKHSTAN - G. Kerimbek,; L. Moldashbayeva,; K. Jrauova,; K. Satymbekova,; Z. Imanbaeva, (Academic Journal of Physical and Chemical Sciences, 2019)
Under the government's strict financial policy that followed the creation of the national currency, market institutions have been gradually formed and matured in the novel macroeconomic environment.The introduction of our own legal tender laid the foundation for our economic successes that came later. This is evidenced by the active development of the financial and credit sector and the Tenge's stability. Tenge is not the first native money in our country. Money was used on the territory of ancient Kazakhstan centuries back. The Turkic rulers in Syrdarya, near Otyrar, and the Turkic peoples in Semirechye produced their own money in VII-VIII centuries. Coin houses operated in Otrar and Isfidjab. The mid-X and VIII centuries witnessed a rapid growth of cities, commodity production and trade. In retail, mostly copper fulus (coins) were used. Gold was also in circulation, not only in coins, but also traded by weight, ie, broken into pieces as needed. In late XIVth century Amir Temir's coins were introduced to Kazakhstan. In addition, Samarkand, Bukhara and Tashkent coins, predominantly copper dinars, were widely used in Kazakh cities. Thus was the history of money in Kazakhstan.Facilitating the country's industrial-innovative development, building on the current achievements, preserving the value of the national currency and achieving financial stability are the most important opportunities for all Kazakhstan citizens.